1069 Does Cerebral Oxygenation Aid in Outcome Prediction in Asphyxiated Newborns Submitted to Hypothermia?. (October 2012) - Costa, P; Sampaio, I; Cardoso, K; Moniz, C; Graça, A
Abstract : Background and Aims: Neurological outcome in asphyxiated newborns submitted to hypothermia is being predicted by aEEG and MRI. The aim of this study was to assess the value of regional cerebral oxygen saturation (rSO2 ) in early outcome prediction and its relation with aEEG and brain MRI. Methods: rSO2 was measured by NIRS INVOS monitor. Newborns were simultaneously monitored with aEEG during hypothermia and rewarming period. Values of rSO2 were analyzed in three groups of predicted outcome (normal, intermediate or abnormal) according to both aEEG pattern at 48h and MRI performed during the second week. Comparisons were done with ANOVA, SPSS19. Results: 21 newborns were monitored. During hypothermia there was a trend towards higher rSO2 in newborns with predicted abnormal outcome. During rewarming there was a significant difference between the normal and abnormal outcome groups (p<0.02). Conclusions: NIRS monitoring may improve the early recognition of newborns with abnormal outcome. Our data suggests that a rSO2 value of 85 during rewarming can be used as a cutoff for predicting abnormal outcome.